Differentiated fatty acid allocation of Daphnia magna helped to maintain their population under food quality deterioration - Wang, Sirui; Liu, Zhengwen; Su, Xiaoqi; Jin, Xiaotong; Jin, Hui; Su, Yaling; Wang, Jianjun; Jeppesen, Erik; Zhang, Xiufeng; Tang, Yali (Frontiers in Microbiology, 2025)
Polyunsaturated fatty acids (PUFAs) are vital to the physiological functioning of crustacean zooplankton. However, cyanobacteria blooms frequently lead to PUFA deficiencies, which poses a substantial challenge to population fitness. Therefore, we hypothesize that D. magna adapt to PUFA-deficient conditions by prioritizing PUFA allocation to somatic growth, and then to offspring during reproduction to ensure population persistence. To test this hypothesis, we applied (compound-specific) 13C labeling to compare the turnover of total carbon and certain groups of fatty acids in Daphnia magna fed with Scenedesmus bijuba for 6 days and then switching to a diet of 13C labeled Microcystis wesenbergii for 6 days (with food quality deterioration) or to a diet of 13C-labeled Scenedesmus (without food quality deterioration), respectively. Fatty acid profiles of D. magna mothers and offspring were also analyzed to reveal their PUFA allocation strategies. Life table parameters from D. magna-feeding Scenedesmus switching to Microcystis were compared with D. magna fed with only Scenedesmus or Microcystis to reveal the effect of PUFA allocation on D. magna performance. Our results showed that with food quality deterioration, D. magna exhibited a significantly lower PUFA and carbon turnover and higher offspring: mother ratios in their PUFA contents. Despite this reduced reproduction, the D. magna switching diets showed no significant different intrinsic increasing rate of populations with those fed only Scenedesmus. Meanwhile, the D. magna switching diets performed significantly better than D. magna fed only Microcystis. These results suggest that differential fatty acid allocation of consumers may serve as an adaptive strategy for population maintenance in food quality deterioration and provide ecological implications with cyanobacterial bloom management and Daphnia reproductive plasticity, which needs further explorations.